Both 3,3′,5-triiodothyronine and 3,5-diodo-L-thyronine Are Able to Repair Mitochondrial DNA Damage but by Different Mechanisms - Cioffi, Federica; Senese, Rosalba; Petito, Giuseppe; Lasala, Pasquale; de Lange, Pieter; Silvestri, Elena; Lombardi, Assunta; Moreno, Maria; Goglia, Fernando; Lanni, Antonia (Frontiers in Endocrinology, 2019)
This study evaluated the effect of 3,5-diiodo-L-thyronine (T2) and 3,5,3’-triiodo-L-thyronine (T3) on rat liver mitochondrial DNA (mtDNA) oxidative damage and repair and to investigate their ability to induce protective effects against oxidative stress. Control rats, rats receiving a daily injection of T2 (N+T2) for 1 week and rats receiving a daily injection of T3 (N+T3) for 1 week, were used throughout the study. In the liver, mtDNA oxidative damage [by measuring mtDNA lesion frequency and expression of DNA polymerase γ (POLG)], mtDNA copy number, mitochondrial biogenesis [by measuring amplification of mtDNA/nDNA and expression of peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α)] and oxidative stress [by measuring serum levels of 8-hydroxy-2’-deoxyguanosine (8-OHdG)] were detected. T2 reduces mtDNA lesion frequency and increases the expression of POLG, and it does not change the mtDNA copy number, the expression of PGC-1α, or the serum levels of 8-OHdG. Therefore, T2, by stimulating the major mtDNA repair enzyme, maintains genomic integrity. Similar to T2, T3 decreases mtDNA lesion frequency but increases the serum levels of 8-OHdG, and it decreases the expression of POLG. Moreover, as expected, T3 increases the mtDNA copy number and the expression of PGC-1α. Thus, in T3-treated rats, the increase of 8-OHdG and the decrease of POLG indicate that there is increased oxidative damage and that the decreased mtDNA lesion frequency might be a consequence of increased mitochondrial biogenesis. These data demonstrate that both T2 and T3 are able to decrease in the liver mtDNA oxidative damage, but they act via different mechanisms.